p65BTK Is a Novel Biomarker and Therapeutic Target in Solid Tumors - Grassilli, Emanuela; Cerrito, Maria Grazia; Bonomo, Sara; Giovannoni, Roberto; Conconi, Donatella; Lavitrano, Marialuisa (Frontiers in Cell and Developmental Biology, 2021)
Bruton’s tyrosine kinase (BTK) is a non-receptor intracellular kinase playing a key role in the proliferation and survival of normal and malignant B-lymphocytes. Its targeting by Ibrutinib, the first specific inhibitor, represented a turning point for the therapy of certain types of B-cell leukemias/lymphomas and several more BTK inhibitors are today in the clinic or advanced clinical trials. BTK expression was successively found to occur also outside of the hematopoietic compartment. In fact, we identified p65BTK, a novel 65kDa isoform lacking an N-term stretch of 86 amino acids (compared to the 77 kDa protein expressed in B cells) as highly expressed in colon cancer patients. We demonstrated that p65BTK is a powerful oncogene acting downstream of the RAS/MAPK pathway and necessary for RAS-mediated transformation. Notably, the kinase domain is conserved and therefore inhibited by the available BTK-targeting drugs (Ibrutinib, Spebrutinib, etc) which we used to demonstrated that p65BTK is an actionable target in drug-resistant colorectal carcinomas (CRC). We found p65BTK expressed also in >50% non-small cell lung cancers (NSCLC) and demonstrated that it is an actionable target in KRAS-mutated/EGFR-wild type drug-resistant NSCLC models (for which no targeted therapy is available). In ovarian cancer patients, p65BTK expression levels correlate with early relapse and shorter progression-free survival, both indicators of resistance to therapy. Notably, Ibrutinib is more effective than standard of care (SOC) therapeutics in in vitro and ex-vivo settings. Finally, we found abundant expression of p65BTK in drug-resistant melanoma models and showed that its targeting restores sensitivity to BRAF and MEK inhibitors and SOC. On the whole, our preclinical data indicate that, depending on the tumor type, BTK inhibitors used alone can be more effective than SOC chemotherapy (ovarian cancer) or can kill drug-resistant tumor cells when used in combination with SOC chemotherapy (colon cancer, NSCLC, melanoma) or targeted therapy (NSCLC, ovarian cancer, melanoma), thus suggesting that p65BTK may be an actionable target in different solid tumors. In addition, our data also give the proof-of-concept for starting clinical trials using BTK inhibitors, alone or in combination, to improve the therapeutic options for solid tumors treatment.